1988
DOI: 10.2331/suisan.54.969
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic variants characteristic of heterozygotes in haploid laver Porphyra sp.

Abstract: Starch gel electrophoresis was carried out to survey the genetic variation in the haploid lavers of the Porphyra sp. claimed to be Porphyra renera. Eleven enzyme loci were resolved and scored. Eight of the eleven loci were monomorphic, while the three loci, catalase (CAT), glucosephosphate isomerase (GPI) and mannosephosphate isomerase (MPI) showed polymorphism. At the Gpi and Mpi loci, a number of lavers had electrophoretic phenotypes characteristic of heterozygotes. In order to compare with Porphyra yezoensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…These differences suggest the possibility that the JHS strain has incidentally acquired a diploid heterokaryon genotype caused by chromosome reorganization, including a fission/fusion process ultimately resulting in cross-fertilization in nature. Fujio et al (1988) reported electrophoretic phenotype characteristics of heterozygotes in the haploid phase of Porphyra sp. and suggested that the plant may be either in the diploid phase or that duplication had occurred in one of the chromosome sets.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest the possibility that the JHS strain has incidentally acquired a diploid heterokaryon genotype caused by chromosome reorganization, including a fission/fusion process ultimately resulting in cross-fertilization in nature. Fujio et al (1988) reported electrophoretic phenotype characteristics of heterozygotes in the haploid phase of Porphyra sp. and suggested that the plant may be either in the diploid phase or that duplication had occurred in one of the chromosome sets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some species display self-fertilization and asexual reproduction (Miura et al, 1979;Fujio et al, 1985Fujio et al, , 1987Gil-Kodaka et al, 1988). Another challenge is the presence of multiple alleles in supposedly haploid gametophytic blades, which can be influenced by divergent partial or complete chromosome copies (Fujio et al, 1988;Varela-Álvarez et al, 2018bVarela-Álvarez et al, , 2021, in chimeric blades (Lindstrom, 1993;Varela-Álvarez et al, 2021) that retain multiple alleles from the conchospores that originated them.…”
Section: Introductionmentioning
confidence: 99%